2021
DOI: 10.1007/s11356-021-15553-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aquaculture on distribution of dissolved organic matter in coastal Jeju Island, Korea, based on absorption and fluorescence spectroscopy

Abstract: In Jeju Island, multiple land-based aquafarms were fully operational along most coastal region. However, the effect of effluent on distribution and behaviours of dissolved organic matter (DOM) in the coastal water are still unknown. To decipher characteristics of organic pollution, we compared physicochemical parameters with spectral optical properties near the coastal aquafarms in Jeju Island. Absorption spectra were measured to calculate the absorption coefficient, spectral slope coefficient, and specific UV… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(8 citation statements)
references
References 53 publications
2
6
0
Order By: Relevance
“…Components similar to component 1 in this study have been attributed to terrestrial humic‐like material (Du et al., 2016; Kothawala et al., 2012; Stedmon et al., 2003; Tank et al., 2011; Xiao et al., 2019). Components similar to component 2 in our study have been attributed to microbially‐derived humic material or phytoplankton degradation products (Kim et al., 2022; Zhang et al., 2010; Zhang, Yin, Liu, et al., 2011). We attribute component 2 to terrestrial humic material that has undergone microbial processing, as identified in Zhou et al.…”
Section: Discussionsupporting
confidence: 72%
“…Components similar to component 1 in this study have been attributed to terrestrial humic‐like material (Du et al., 2016; Kothawala et al., 2012; Stedmon et al., 2003; Tank et al., 2011; Xiao et al., 2019). Components similar to component 2 in our study have been attributed to microbially‐derived humic material or phytoplankton degradation products (Kim et al., 2022; Zhang et al., 2010; Zhang, Yin, Liu, et al., 2011). We attribute component 2 to terrestrial humic material that has undergone microbial processing, as identified in Zhou et al.…”
Section: Discussionsupporting
confidence: 72%
“…Additionally, the TDN concentration (0.13 ± 0.03 mg/L) in the study area, which can act as a marker of aquaculture activity, was lower than that recorded from drainage samples (0.74 ± 0.46 mg/L) directly obtained at the discharge outlet in the aquafarm region and in the coastal water near the aquafarm outlet (0.25 ± 0.26 mg/L). However, it was similar to the TDN concentration observed at a control site (0.12 ± 0.05 mg/L) located more than 5 km away from the aquafarms (Kim et al, 2022). Furthermore, in contrast to the findings reported by Oh et al (2021) for areas influenced by fresh/saline groundwater and landbased fish farm wastewater within 0.5 km of the coast, we observed that the DIN concentration did not follow the expected pattern of a decrease with an increase in salinity (Table S2), exhibiting an increase instead (Spearman's r = 0.290, p < 0.01).…”
Section: Spatiotemporal Distribution Of Domsupporting
confidence: 80%
“…Indeed, nutrient availability in Jeju's coastal waters is strongly related to land-based, anthropogenic activities, such as land-operated fish farms which are present in the vicinity of SH. Wastewater from land-operated fish farms accounts for up to 95% of the seawater ammonium (Kwon et al, 2022), increasing coastal DIN and DIP concentrations (Choi et al, 2021), and generally contributes significantly to the nitrogen budget in the coastal waters of Jeju (Koh et al, 2013;Kim et al, 2022b). Sea water enriched in ammonium is preferred by coralline algae, which dominate SH (Nguyen et al, 2020;Kwon et al, 2022).…”
Section: Discussionmentioning
confidence: 99%